Measurement Of Morphological Characteristic Of Sudanese Female Pelvis Compare To Other Nationalities. - Fatima Dahi Mohammed; Al Taher Osman Ali; Hamed Osman; Ikhlas Abdelaziz Hassn; Asma Ibrahim Ahmed (Asian Journal of Medical Radiological Research, 2013)
The main objectives of this study were to establish standard measurement of Sudanese female pelvis and comparing the measurements with othernationalities in order to develop a Sudanese reference document. The study also aimed to describe the, characteristic of Sudanese female pelvis,specially the birth canal, and to determine the prevalence of different anatomical variation in different parts of the Sudan. The result of this studyshowed that there were two mains pelvic types in the Sudan, out of four known types in the world, the two types were: The anthropoid pelvis (ovalbirth canal) and the gynaeocoid pelvis (rounded birth canal). The other types of pelves were not common in Sudan. The two types presented asfollowing: In north of Sudan 68% of cases were anthropoid while 32% of cases were gyneacoid. In South of Sudan, 30% of cases were anthropoidand 70% of cases were gyneacoid. In west of Sudan 49.3% of cases were anthropoid and 50.7% of cases were gyneacoid. In East of Sudan, 22%of cases were anthropoid and 78% of cases are gyneacoid. In conclusion, the anthropoid and gynaecoidpelves are common in Sudan. While theplatopelloid and android pelves are rare